MOM IS HERO: PRENATAL-POSTNATAL CALENDAR SEBAGAI UPAYA PENCEGAHAN STUNTING DENGAN PENDEKATAN THEORY OF PLANNED BEHAVIOR - Safitri, Bella; Oktavia, Regina; Khairunnisa, Khairunnisa; Sarah, Devi; Noval; Melviani, Melviani; Noval, Noval (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Stunting is a problem that has become a national concern in Indonesia. stunting can not only reduce the quality of human resource (HR) in Indonesia but also can threaten the nation’s competitiveness (Simamora, 2021). Based on Basic ealth Research Data the national stunting prevalence rate in 2021 is 244% (Kemenkes, 2022). The aim of tis research is to describe the behavior of pregnant women and breastfeeding mothers towards “Mom is Hero” calendar. The research method uses a pre-experimental method with a One Group pretest-posttest design. Then the data was analyzed using the Pair t-test. In this study the t significance result for the variables of attitude, subjective norms and preceived behavioral control were 0.000.